Risk Scorecard w ujęciu controllingowym jako instrument ograniczania ryzyka działalności organizacji - Bieńkowska, Agnieszka; Kral, Zygmunt; Zabłocka-Kluczka, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The topicality of a problem of construction instruments, which will permit to objectivize the risk assessment at organization, is justified. The RISK SCORECARD in the controlling grasp as an instrument of limiting the organization activity risk is proposed. Its essence and assumptions are pointed. The procedure of creating the RISK SCORECARD for responsibility centres is introduced. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 13-26